Analysis of Spatiotemporal Variation Characteristics of Rainfall Erosivity in Guangdong Province from 1960 to 2018 - DENG Panpan; QIN Beilei; DU Liya (Renmin Zhujiang)
In order to analyze the spatiotemporal variation characteristics of rainfall erosivity in Guangdong Province,the daily rainfall data from 86 stations in Guangdong Province during 1960—2018 were systematically studied by using methods such as the daily rainfall erosivity model,Mann-Kendall trend,and wavelet analysis.The results show that the mean rainfall erosivity in Guangdong Province from 1960 to 2018 is 9 839 (MJ·mm)/(hm2·h·a),and it fluctuates in the range of 7 137~14 339 (MJ·mm)/(hm2·h·a).In terms of spatial distribution,the rainfall erosivity gradually increases from north to south and is strong in coastal areas.Most stations in Guangdong Province show a rising trend.The interpolation results show that except for several regions in eastern Guangdong Province,the rainfall erosivity in other regions all increases.The periodic analysis shows that the principal variation period of annual rainfall erosivity from 1960 to 2018 is seven years,and there is an oscillation period of two to eight years.This study can provide some guidance for water and soil conservation and other works in Guangdong Province.